Challenging the Integrity of Rhythmic Maternal Signals Revealed Gene-Specific Responses in the Fetal Suprachiasmatic Nuclei - Lužná, Vendula; Houdek, Pavel; Liška, Karolína; Sumová, Alena (Frontiers in Neuroscience, 2021)
During fetal stage, maternal circadian system sets the phase of the developing clock in the suprachiasmatic nuclei (SCN) via complex pathways. We addressed the issue of how impaired maternal signaling due to a disturbed environmental light/dark (LD) cycle affects the fetal SCN. We exposed pregnant Wistar rats to two different challenges – a 6-h phase shift in the LD cycle on gestational day 14, or exposure to constant light (LL) throughout pregnancy – and detected the impact on gene expression profiles in 19-day-old fetuses. The LD phase shift, which changed the maternal SCN into a transient state, caused robust downregulation of expression profiles of clock genes (Per1, Per2, Nr1d1), clock-controlled (Dbp) genes, as well as genes involved in sensing various signals, such as c-fos and Nr3c1. Removal of the rhythmic maternal signals via exposure of pregnant rats to LL abolished the rhythms in expression of c-fos and Nr3c1 in the fetal SCN. We identified c-fos as the gene primarily responsible for sensing rhythmic maternal signals because its expression profile tracked the shifted or arrhythmic maternal SCN clock. Pathways related to the maternal rhythmic behavioral state were likely not involved in driving the c-fos expression rhythm. Instead, introduction of a behavioral rhythm to LL-exposed mothers via restricted feeding regime strengthened rhythm in Vip expression in the fetal SCN. Our results revealed for the first time that the fetal SCN is highly sensitive in a gene-specific manner to various changes in maternal signaling due to disturbances of environmental cycles related to the modern lifestyle in humans.